sPinal cOrd neUromodulatioN to treat Cerebral palsy in pEdiatrics: POUNCE Multisite Randomized Clinical Trial - Girshin, Kristin; Sachdeva, Rahul; Cohn, Richard; Gad, Parag; Krassioukov, Andrei V.; Edgerton, V. Reggie (Frontiers in Neuroscience, 2023)
Introduction Cerebral palsy (CP) affects up to 4 children in 1,000 live births, making it the most common motor disorder in children. It impairs the child’s ability to move voluntarily and maintain balance and posture, and results in a wide range of other functional disorders during early development impairments in various sensory modalities, e.g., vision, hearing ability and proprioception. Current standard of care therapy focuses on symptom management and does not mitigate the progression of many of these underlying neurological impairments. The goal of this trial is to conduct a prospective multicenter, double-blinded, sham-controlled, crossover, randomized control trial to demonstrate the safety and efficacy of noninvasive spinal cord neuromodulation (SCiP™, SpineX Inc.) in conjunction with activity-based neurorehabilitation therapy (ABNT) to improve voluntary sensorimotor function in children with cerebral palsy. Methods and analysis Sixty participants (aged 2–13 years) diagnosed with CP classified as Gross Motor Function Classification Scale Levels I-V will be recruited and divided equally into two groups (G1 and G2). Both groups will receive identical ABNT 2 days/wk. G1 will initially receive sham stimulation, whereas G2 will receive therapeutic SCiP™ therapy for 8 weeks. After 8 weeks, G1 will cross over and receive therapeutic SCiP™ therapy for 8 weeks, whereas G2 will continue to receive SCiP™ therapy for another 8 weeks, for a total of 16 weeks. Primary and secondary outcome measures will include Gross Motor Function Measure-88 and Modified Ashworth Scale, respectively. Frequency and severity of adverse events will be established by safety analyses. Ethics and dissemination The trial is registered on clinicaltrials.gov (NCT05720208). The results from this trial will be reported on clinicaltrials.gov, published in peer-reviewed journals and presented at scientific and clinical conferences.